Analisis Perbedaan Penggunaan Transaksi Tunai Dan Non Tunai (E-Money) Pada Mahasiswa UPN “Veteran” Jawa Timur - Diva Shafitri; M Taufiq (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
Money is something important in a country. Due to the rapid development of money in Indonesia, the payment system is also growing into two parts, cash and non-cash payments. Students also use it. However, differences in gender, UKT group, and area of ​​residence can affect the differences in transactions between each other. Therefore, this study discusses the differences in the frequency of transactions and the nominal value of transactions at UPN "veteran" East Java students. This study uses a quantitative approach to collect data using a questionnaire survey method. A total of 100 students have e-money applications. For data analysis, this study used a t-test analysis of two different samples, namely the independent sample t test difference test. The results of this study indicate that there are no differences in cash and non-cash transactions in the frequency of transactions when viewed in terms of gender, household group and area of ​​residence. Meanwhile, in the nominal value of the transaction, there are differences in terms of the UKT group and gender.